Working in the Midst of Ideological and Cultural Differences: Critically Reflecting on Youth Suicide Prevention in Indigenous Communities - White, Jennifer (Canadian Journal of Counselling and Psychotherapy, 2008)
Many non-Aboriginal practitioners are interested in working effectively with Aboriginal youth, families, and communities. Honouring Indigenous ways of knowing and being informed by a critical consciousness regarding the influence of history, politics, and social forces in the emergence of suicidal behaviour among Aboriginal youth are central to this work. By uncovering assumptions and locating suicide prevention practice withinspecific discourses, this article demonstrates the relevance and value of critical reflection. Qualities of curiosity, collaborative meaning-making, joint knowledge construction, and ethical engagement are valuable resources for counsellors practicing at the clinical or community level.